Climate Change on the Tourism Industry in Batulayang Tourism Village Destinations Using Swot Review - Awaloedin, Dipa Teruna; Wulansari, Wuri; Asyari, Asyari; Pradini, Gagih (International Journal of Education, Information Technology, and Others, 2024)
Tourism, as a significant global economic sector, has become an integral part of many people's lives. However, climate change poses a serious threat to the tourism industry, including in Desa Wisata Batulayang, a tourism destination known for its natural beauty and cultural richness. This study employs a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to identify the strengths, weaknesses, opportunities, and threats faced by Desa Wisata Batulayang in addressing climate change. It also explores the role of Public Relations (PR) in handling these challenges and devising strategies to help this tourist village survive and thrive. The findings reveal that Desa Wisata Batulayang has strengths in its natural beauty, local wisdom, and various tourist attractions. However, it also has weaknesses, such as high dependency on environmental conditions and infrastructure that may not be fully prepared for climate change. Opportunities for the village lie in developing alternative tourism and sustainable tourism, while threats include extreme weather, infrastructure damage, and the risk of natural disasters. Public Relations plays a critical role in addressing the threats of climate change. PR can educate tourists and the community, disseminate information about adaptation efforts, and promote a positive image through campaigns emphasizing sustainable tourism. Additionally, PR can collaborate with various stakeholders to support climate change mitigation and adaptation programs. In conclusion, although climate change presents serious challenges to the tourism industry in Desa Wisata Batulayang, with appropriate strategies and support from various parties, this village can strengthen its resilience and continue to be an attractive tourist destination. Recommendations include improving management quality, diversifying tourism products, preparing emergency plans, and conducting regular evaluations and monitoring. By taking these steps, Desa Wisata Batulayang can become an example of a resilient and sustainable tourist village amid the challenges posed by climate change